2021
DOI: 10.1093/intqhc/mzab103
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of imaging decisions for low back pain presenting to the emergency department: a retrospective chart review study

Abstract: Background Imaging for low back pain is widely regarded as a target for efforts to reduce low value care. We aimed to estimate the prevalence of overuse and underuse of lumbar imaging in the Emergency Department. Methods Retrospective chart review study of five public hospital Emergency Departments in Sydney, Australia, in 2019/20. We reviewed the clinical charts of consecutive adult patients who presented with a complaint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is unclear whether the proportion diagnosed with serious pathology without imaging suggests judicious use, inappropriate delays in imaging, or the fact that some patients had performed outside of ED, for example arranged by their GP, prior to presenting. Recent studies suggest that underuse of imaging happens in approximately 4.3% of encounters for LBP 22 . Further research that explores clinical features alongside use of imaging will help determine the extent of imaging underuse in those with specific spinal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the proportion diagnosed with serious pathology without imaging suggests judicious use, inappropriate delays in imaging, or the fact that some patients had performed outside of ED, for example arranged by their GP, prior to presenting. Recent studies suggest that underuse of imaging happens in approximately 4.3% of encounters for LBP 22 . Further research that explores clinical features alongside use of imaging will help determine the extent of imaging underuse in those with specific spinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that underuse of imaging happens in approximately 4.3% of encounters for LBP. 22 Further research that explores clinical features alongside use of imaging will help determine the extent of imaging underuse in those with specific spinal conditions. Similarly, we cannot say from these data whether those with NSLBP received 'unnecessary' imaging.…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
“…Clinician investigators who review the appropriateness of imaging will use a standardised survey in REDCap to extract data and score appropriateness. This process is informed by our previous work 35. We anticipate we will require 10–20 clinicians to assist with case note reviews.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…We chose this composite outcome because it is a meaningful metric to ED clinicians. Clinician researchers will perform chart reviews every month for all participants who present with low back pain and receive imaging to understand and code if it was non-indicated imaging (ie, imaging provided in the absence of clinical features of serious pathology) using reliable methods we have published 35. Opioids provided or prescribed at discharge for patients diagnosed with ‘non-serious’ low back pain (ie, low back pain with non-specific cause or low back pain with neurological signs and symptoms—see online supplemental table 1) will be coded as low value.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…However, surveys have shown that, despite medical guidelines, the diagnostic imaging of the lumbar spine remains subject to the personal preferences of the healthcare provider [ [ 11 ]]. Static X-rays are still commonly performed in emergency departments [ [ 12 ]].…”
Section: Introductionmentioning
confidence: 99%